Patterns of Livelihood Diversification among Kamnarok National Reserve adjacent Communities in Baringo County, Kenya (Journal of Sustainability, Environment and Peace, 2020)
Evidence abounds that rural households do not only receive a significant proportion of their livelihoods from agriculture, but also from non-farm sources through diversification. The purpose of the study was to assess patterns of livelihood diversification and human-wildlife conflicts among communities living near Kamnarok NR in Baringo, Kenya. A qualitative approach using exploratory research design was adopted. Questionnaire survey and observation were used as data collection tools and census sampling of the three locations of Barwesa ward in Baringo County formed the unit of analysis. Likert scale type of questionnaire provided options for scoring in the measurement of the prevailing livelihood in the study area. Cronbach’s Alpha was used to test reliability of the items found with the significance level at 0.7. Descriptive statistics, Factor analysis and Pearson Correlation were used to analyze data. The findings reveal that Kamnarok NR adjacent community exhibit variations in diversified livelihood portfolios pursued as a measure to ameliorate themselves from the risks of agro-climatic vulnerabilities and livelihood risks brought by wildlife. Furthermore, agro-climatic vulnerabilities, general push factors and physical asset possessions were observed to be livelihoods diversification motivational factors. Furthermore, from the six factors analyzed, the majority explained patterns of livelihood diversification. For example, four factors (66.7%) explained patterns of diversification and at least a third of the factors (33.3%) were insignificant in explaining livelihood diversification. General pull factors thought to be the main motivational factor for livelihood diversification was insignificant. Physical asset possessions and contextual factors, however, were the most important factors in explaining patterns of livelihood diversification. Physical asset possession was more significant than wildlife-related factors suggesting that the existence and possession of an array of assets such as land, livestock, buildings and machinery, human labour and adequate capital are the principal motivating factors for diversified livelihoods in Kamnarok NR adjacent areas. Quantifying and characterizing factors driving patterns of livelihood diversification among communities living in biodiversity-rich rangelands can complement livelihood risk data and result in robust human-wildlife mitigation strategies.
Keywords: Biodiversity conservation; human wildlife conflicts; Livelihood diversification; Livelihood strategies